Lead-Free (Ba0.70Sr0.30)TiO3-Modified Bi0.5(Na0.80K0.20)0.5TiO3 Ceramics with Large Electric Field-Induced Strains - Jaita P. (2017)
Â© 2016 The American Ceramic Society. The dielectric, ferroelectric, and electric field-induced strain behavior of Bi 0.5 (Na 0.80 K 0.20 ) 0.5 TiO 3 (BNKT) ceramics modified with (Ba 0.70 Sr 0.30 )O 3 (BST) were investigated as a function of composition and temperature. The ceramic samples were synthesized by a solid-state mixed oxide method and sintered at 1125Â°C for 2 h. The XRD and Raman spectra showed coexisting rhombohedral and tetragonal phases throughout the entire compositional range with the tetrago nal phase becoming dominant at higher BST concentrations. For all compositions, the temperature dependence of the dielectric spectra revealed a frequency dependence that is characteristic of a relaxor mechanism. This suggests that these ceramics lacked long-range order and it appears that the maximum disorder was observed for the composition with 5 mol% BST (BNKT-0.05BST sample). This was evidenced by the observation of pinched hysteresis loops, even at room temperature, and a significant decrease in the P r and E c values which resulted in large electric field-induced strains (S max ) of 0.40% and a normalized strain coefficient (d 33 ∗ - = S max /E max ) of 732 pm/V. This significant strain enhancement at the composition of x = 0.05 may be attributed to both a composition-induced structural phase transition and a field-induced relaxor to ferroelectric phase transition.